Peran Masyarakat dalam Menjaga Keberagaman dan Kerukunan di Gampong Peunayong Kota Banda Aceh - Maulana , Heri; Safrina; Anggita, Daniya; Amal, Muchlasul (Program Studi Ilmu Administrasi Negara Bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research aims to analyze the role of the community in maintaining and developing diversity and harmony in Gampong Peunayong, Banda Aceh City. Using qualitative research methods and a descriptive approach, this study collected data through interviews, observation, and documentation. The results showed that the people of Peunayong Village have a strong commitment in preserving local cultural values and customs, as well as respecting the norms and customs that apply. existing customs. Interaction between ethnic groups, especially between the Acehnese and Chinese communities, is characterized by harmony and mutual respect, despite differences in cultural and religious backgrounds. Awareness of the importance of inter-religious harmony and diversity is the cornerstone of people's daily lives. This research also identifies the challenges they face in maintaining harmony, such as differences in viewpoints and the potential for conflict. The people of Gampong Peunayong are able to overcome these differences and build an inclusive society. It is hoped that these findings can provide insights for policy makers and the wider community in efforts to improve harmony and diversity in other areas.